Speaking One Language with Different Accents: A Review on Adoption of International Accounting and Auditing Standards - Suyanto Suyanto (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
The objective of this study is to comprehend different practices of accounting and auditing across countries. Although over 120 countries use similar accounting and auditing standards, resulting from converging towards IFRS and ISA respectively, a difference of accounting and auditing practices still exists. It needs a comprehensive theory or analytical framework to explain such differences. Yet, there is still a limited overarching theory and comprehensive analytical framework to explain different accounting and auditing practices. Hofstede's work on culture, which is widely used in accounting and auditing research, may be useful to comprehend various accounting and auditing practices. Alternative explanations using political and economic factors are also often proposed to explain the dissimilarities. These fragmentary approaches seem to result in lack of understanding on the issue.  Seeking theories or analytical tools to provide an enhanced explanation of why accounting and auditing practiced differently may be worthwhile avenues.